Information technology. International standardized profiles TB, TC, TD and TE. Connection-mode transport service over connection-mode network service. Subnetwork-type dependent requirements for network layer, data link layer and physical layer concerning permanent access to a packet switched data network using virtual calls Part 9, (15th January 1993) - British Standards Institution,
No abstract available